Development of a Problem-Based Learning Social Studies Teaching Module Containing the Local Wisdom of Pemalang Batik to Increase Middle School Students' Motivation and Learning Engagement - Munasikhah Munasikhah; Sitti Hartinah; Hanung Sudibyo (PT. Anagata Sembagi Education, 2025)
Social Studies (IPS) learning plays a strategic role in shaping students' social understanding, character, and cultural awareness. However, social studies learning at the junior high school level still faces the problem of low learning motivation due to conventional approaches that lack context. This condition is also found in Pemalang Regency, which has unique socio-economic characteristics and local wisdom potential in the form of batik that has not been optimally utilized in learning. This study aims to develop a Problem-Based Learning (PBL) model for social studies education that incorporates the local wisdom of Pemalang batik as an effort to improve the relevance and quality of learning. The research used a Research and Development (R&D) approach with the ADDIE model, limited to the Analyze, Design, and Develop stages. The research subjects included subject matter experts, learning model experts, and social studies teachers at three junior high schools in Pemalang Regency. Data collection was conducted through document analysis, limited interviews, literature studies, and expert validation. Data analysis was conducted qualitatively and quantitatively using a four-point Likert scale. The results showed that the PBL-based social studies learning module containing local wisdom of Pemalang Batik met the criteria of